Upaya Perlindungan Hukum Terhadap Anak Sebagai Korban Kekerasan Seksual (Studi Kasus di Polda Bali) - Ida Ayu Sadnyini; Sang Putu Wedha Rama (Universitas Pendidikan Nasional, 2022)
Child problems that often occur to children are acts of sexual violence against children which can be in the form of physical or psychological violence. Sexual violence against children needs serious attention considering the consequences of sexual violence against children will cause children to experience prolonged trauma. Trauma can endanger the mental development of children so that children cannot grow and develop properly. Cases of crimes of sexual violence against children where the perpetrators are adults and most of them are known to the victims. In general, sexual violence is a sexual satisfaction that is obtained by someone from having sex with children. The purpose of this study is to find out and analyze the legal protection for children as victims of sexual violence provided by the Bali Police and the form of sanctions given to perpetrators of criminal acts. sexual violence against children. This study uses empirical or sociological research methods with a juridical approach. The results showed that the legal protection provided by the PPA Unit was in the form of legal and psychiatric assistance starting from the investigation process to the judicial process. The imposition of sanctions given to adult perpetrators in accordance with the provisions of Law no. 35 of 2014. For perpetrators who are minors, efforts are made through diversion, if diversion is not possible, it will be processed in accordance with the provisions contained in Law no. 11 of 2012.